Effectiveness of nurse-led volunteer support and technology-driven pain assessment in improving the outcomes of hospitalised older adults: protocol for a cluster randomised controlled trial - Saunders, Rosemary; Crookes, Kate; Seaman, Karla; Ang, Seng Giap Marcus; Bulsara, Caroline; Bulsara, Max K; Ewens, Beverley; Gallagher, Olivia; Graham, Renee M; Gullick, Karen; Haydon, Sue; Hughes, Jeff; et al. (BMJ Journals, 2022)
Introduction: Hospitalised older adults are prone to functional deterioration, which is more evident in frail older patients and can be further exacerbated by pain. Two interventions that have the potential to prevent progression of frailty and improve patient outcomes in hospitalised older adults but have yet to be subject to clinical trials are nurse-led volunteer support and technology-driven assessment of pain.